Bibliometric profile of scientific production in Odontología Sanmarquina journal, 2005-2014 - Castro Rodríguez, Yuri (2017)
Objective: To evaluate a bibliometric profile of the scientific productivity in the journal Odontología Sanmarquina. Materials and method: A descriptive study was designed; the scientific articles published in the journal from the years 2005 to 2014 were analyzed. Scientific productivity per year, type, design and theme of the articles was analyzed and also the number of authors, the first author affiliation, foreign co-authorship, the bioethical permission and funding of these research. The search for articles was made through a manual analysis via the portal web of the journal. Results: 200 articles published over a period of 10 years were analyzed, 59% were original articles, 25% clinical reports and literature reviews were the 16%. The most prevalent themes of the studies were related to basic science (43.5%) and Periodontology (13%). Only 3.5% of the publications had a foreign co-authored and 99.5% of them lacked a bioethical permission. Conclusions: The results indicate the basic sciences and periodontics is the main subject of publication in the journal, and that most of them are derived from original research.